Perspektif Good Governance Dalam Revitalisasi Pasar Rakyat Gianyar - Kristinawati, Ni Luh (Lenggogeni Data Publishing, 2025)
The purpose of this study is to analyze the perspective of good governance in the revitalization of the Gianyar People's Market. The research method used is qualitative descriptive with data collection techniques including observation, interviews, and documentation. Based on the results of field research, it was studied using the theory of good governance by Tjokroamidjojo (2000) which consisted of: (1) Accountability, (2) Transparency, (3) Openness, (4) Rule of law, and (5) Justice. The results of the study show that the application of good governance principles has been implemented by the management after the revitalization of the market but has not been fully implemented optimally. Shortcomings are still found, namely in the accountability indicator, the trader's economy is not fully accounted for as it used to be, the transparency indicator where there is no awareness of the management using social media to promote the superiority of Gianyar People's Market traders, the openness indicator is not fully responsive in overcoming traders' complaints, the indicator of the rule of law is still not complied with by traders where there are traders who are in arrears or do not pay levies, and the indicators of justice are not balanced because the quiet activity of traders and buyers is triggered by the operation of the relocation market, namely the Samplangan Market is still open. Recommendations for these problems include strengthening commitment and increasing creativity, fostering sensitivity to community participation, self-empowerment, compaction planning, and providing smart seller education. Keywords: Economy, Good Governance, Market Revitalization Abstrak Tujuan penelitian ini adalah menganalisis perspektif good governance dalam revitalisasi Pasar Rakyat Gianyar. Metode penelitian yang digunakan yaitu deskriptif kualitatif dengan teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian lapangan dikaji menggunakan teori good governance oleh Tjokroamidjojo yang terdiri dari: (1) Akuntabilitas, (2) Transparansi, (3) Keterbukaan, (4) Supremasi hukum, dan (5) Keadilan. Hasil penelitian menunjukan bahwa penerapan prinsip-prinsip good governane telah diselanggarakan oleh pihak pengelola pasca revitalisasi Pasar namun belum sepenuhnya terlaksana dengan optimal. Kekurangan masih ditemukan yaitu pada indikator akuntabilitas masih belum mempertanggungjawabkan perekonomian pedagang belum sepenuhnya seperti dulu, indikator transparansi dimana belum adanya kesadaran pihak pengelola menggunakan media sosial mempromosikan keunggulan pedagang Pasar Rakyat Gianyar, indikator keterbukaan belum sepenuhnya responsif dalam mengatasi keluhan pedagang, indikator supremasi hukum masih kurang dipatuhi oleh pedagang dimana terdapat pedagang yang menunggak atau tidak membayar retribusi, dan indikator keadilan belum seimbang karena sepinya aktivitas pedagang dan pembeli dipicu oleh operasional pasar relokasi yaitu Pasar Samplangan masih dibuka. Rekomendasi atas permasalahan tersebut meliputi memperkuat komitmen dan menambah kreativitas, menumbuhkan kepekaan partisipasi masyarakat, self-empowerment, compaction planning, serta memberikan education smart seller. Kata Kunci: Perekonomian, Good Governance, Revitalisasi Pasar